Two-Dimensional CFD Modeling of Hysteresis Behavior of MR Dampers. (10th April 2019) - Guo, Pengfei; Xie, Jing
Abstract : So far, most previous studies on the nonlinear hysteresis analysis of ER/MR dampers have been limited to one-dimensional modeling techniques. A two-dimensional (2D) axisymmetric CFD model of MR dampers is developed in this work. The main advantage of the proposed 2D model of MR dampers lies in that it can be used to predict dynamic behavior of MR devices of arbitrary geometries. The compressibility of MR fluids is the main factor responsible for the hysteresis behavior of MR dampers, and it has been rarely investigated in previous multidimensional modeling of MR damper. In our model, the compressibility of MR fluids is taken into account by the two-dimensional constitutive model which is extended from a previous one-dimensional physical model. The model is solved by using the finite element method, and the movement of the piston is described by the moving mesh technique. The MR damper in a reference is simulated, and the model predictions show good agreement with the experimental data in the reference.